DEFORMATION IN THE LIGHT BR ISOTOPES - Griffiths, A; Ashworth, C; Grant, I; Rikovska, J; Stone, N; Walker, P; Walters, W; White, J (Kluwer Academic Publishers, 1988)
The nuclear ground state spins of the odd-A Br nuclides75, 77, 79Br with Z=35 are all 3/2-. Nilsson orbital calculations show that the 35th proton occupies the f5/2 [301]3/2- orbital for ε<0.20 and the p3/2 [312]3/2- orbital at larger deformations. The magnetic moments of these two states differ by a factor of two, giving clear evidence for the magnitude of the ground state deformation. Low Temperature Nuclear Orientation measurements made in Oxford and Bonn on76, 77gBr Fe prepared at ISOLDE, and on line at the SERC Daresbury Laboratory on72, 74m, 75Br Fe, have yielded the magnetic moments of these isotopes, using a two non-zero field model with magnetic hyperfine fields of +81.38(6) T and 26(2) T. The spin of the73Br ground state is also deduced. An interpretation of the ground state configurations of these isotopes is given. © 1998 J.C. Baltzer A.G., Scientific Publishing Company.